Rheological investigation and simulation of a debris-flow event in the Fella watershed - M. A. Boniello; C. Calligaris; R. Lapasin; L. Zini (Natural Hazards and Earth System Sciences, 2010)
To set an approach for the future territorial planning, the Geological Survey of Friuli Venezia Giulia Region, through the researchers of Trieste University, started a program of debris-flow risk analysis using Flo-2D software as tool to delimit the hazardous areas. In the present paper, as a case study, a debris flow, called Fella sx, occurring in a torrent catchment was analyzed. The choice was due to the abundance of information about past events, inundated areas, rain fall, geology and to its representativeness. An initial back-analysis investigation identified a couple of representative rheological parameters. Riverbed samples were collected, sieve analyses were performed and rheological tests were carried out on the fraction finer than 0.063 mm using a rotationally controlled stress rehometer equipped with the serrated parallel plate geometry. The shear dependent behaviour was examined at different concentrations ranging from 33 to 48%, by weight. Viscosity data treatment was performed to determine the most suitable rheological model to provide the best approximation of the debris-flow behaviour. The rheological parameters, derived from experimental data, were used and compared with those obtained through the back-analysis and with the real inundated area. Data obtained through rheological analysis are useful in constructing scenarios of future events where no data for back-analysis are available.